THE EFFECT OF COMMUNICATIVE LANGUAGE TEACHING (CLT) METHOD ON ENGLISH COMPREHENSION FOR STUDENTS AT THE FIFTH GRADE OF SD KARTIKA X-3 - Kartyca Naya; Caroline V. Katemba (Journal of Language Pedagogy, 2011)
This study incolves the students at the fifth grade of SD Kartika X-3 as the subject ofthe research. And the writer teaches them through Information Gap, games, Pair Work, etcetera. A pre and post test was administered. The data was analyzed by suing t-test. Theresult shows that students’ English comprehension had improved by using CommunicativeLanguage TGeaching (CLT) method at the coefficient t counted =2265>t table = 1667 withthe significance of level in 0.05 and the degree freedon is 32 (df=n-1). The students’responses toward the post-test given prove that Communicative Language Teaching (CLT)method is effective to improve students’ English comprehension ability.